C-Kit/c-Kit ligand interaction of bone marrow endothelial progenitor cells is influenced in a cigarette smoke extract-induced emphysema model. (1st August 2013) - He, Shengdong; He, Zhihui; Chen, Yan; Ye, Jiru; Zong, Dandan; Zhang, Yan; Chen, Ping
ABSTRACT: Background : Smoking causes lung endothelial cell apoptosis and emphysema. Derived from bone marrow, circulating endothelial progenitor cells (EPCs) maintain vascular integrity by replacing and repairing damaged endothelial cells. Smoking influences the number of circulating EPCs. Recruitment of EPCs from bone marrow to peripheral blood depends on the interaction of c-Kit/soluble c-Kit ligand (sKitL). We hypothesized that smoking might influence c-Kit(+) EPCs/sKitL interaction in bone marrow in the development of smoking-related emphysema. In this study, we used a cigarette smoke extract (CSE)-induced emphysema model. Methods : Mice were injected intraperitoneally with PBS/CSE and sacrificed at day 28. Lung function and pathology of lung tissue were measured to characterize the model. Expressions of c-Kit in the lung tissue were assayed. Bone marrow cells were isolated by red blood cell lysis. EPCs/c-Kit(+) EPCs in nonred blood cells were analyzed by flow cytometry. Expressions of KitL and MMP-9, and activity MMP-9 in bone marrow were measured. Results : Our data demonstrated that gene and protein expressions of c-Kit were decreased in the lung tissue in this model. Compared with the control group, the number of bone marrow nonred blood cells was unchanged following CSE treatment, while the depletion of bone marrow EPCs/c-Kit(+) EPCs was significant. The level of sKitL was reduced in the bone marrow in the model. The reduction of sKitL was associated with deregulated KitL expression and decreased MMP-9 activity. Conclusions : The interaction between c-Kit and sKitL in bone marrow EPCs, a critical step in endothelial repair, is negatively affected in a CSE-induced emphysema model.